Penerapan Metode TOPSIS untuk Menentukan Kelayakan Perpustakaan Sekolah Diakreditasi - sukamto, sukamto; Id, Ibnu Daqiqil; Jukris, Avisha Delinda (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
School libraries should be accredited with the aim of improving the quality of libraries. Pekanbaru City Library and Archives Service (DISPUSIP) in determining a school library that deserves to be accredited is still done manually, namely DISPUSIP went directly to the field to monitoring the library in the school and the data collection still used manual entries. Meanwhile, a lot of data must be collected, causing the data to be inaccurate and take a long time. For this reason, a decision support system (DSS) is needed. The data used are nine junior high schools both public and private as an alternative. While the criteria refer to the school library accreditation instrument issued by the National Library (Perpusnas) consisting of six criteria, namely collections, library facilities and infrastructure, library services, library staff, library administration and management, and reinforcement. Data analysis using the TOPSIS method by steps of determining the decision matrix, normalization matrix, calculating both positive and negative ideal solutions, calculating the distance to the ideal solution, calculating preference values, and ranking. The results obtained for the SMP library are Sek 4, Sek 1 and Sek 5 which are eligible for accreditation.